OP4 Accessing unplanned and emergency health services – experiences of asylum seekers, refused asylum seekers and refugees living in wales. Issue 10 (24th September 2019) - Khanom, Ashrafunnesa; Evans, Bridie; Alonazi, Wedad; Glendenning, Alex; Jones, Matthew; John, Ann; Khan, Talha; Kingston, Mark Rhys; Manning, Cathrin; Moyo, Sam; Porter, Alison; Rhydderch, Melody; et al.
Abstract : Background: Numbers of asylum seekers and refugees living in Wales have increased sharply. Many are liable to have unmet health needs and difficulty accessing services. We investigated the experience of, and access to, unplanned and emergency health services by asylum seekers, refugees and those refused asylum living in Wales. Method: We surveyed 210 asylum seekers, refused asylum seekers and refugees and conducted eight focus groups with 57 participants (with interpreters present when necessary) to explore experiences. We used descriptive statistics to analyse survey data and framework analyses to analyse interview data. Results: Survey data showed awareness of unscheduled health services was mixed. Best known was the 999 ambulance service (72% reportedly had heard of and could contact this outside daytime hours). NHS111 was familiar to 36% but just a quarter (26%) had heard of and could contact GP out-of-hours services. Fewer than half of respondents (44%) knew of the Emergency Department. 26% reported using a health service out-of-hours. Focus group respondents with little English reported difficulty explaining their health needs, particularly in emergencies and when seeking telephone help through 999 and 111 calls. Others said they used emergency services if they did not know how to access routine and out-of-hours care or if they felt their efforts to see a GP did not resolve their problem. Conclusion: Language barriers and poor knowledge of UK health systems mean asylum seekers, refused asylum seekers and refugees use emergency health services to meet needs which could be seen and treated in routine primary services. Language barriers using phone lines may also result in paramedic attendance or conveyance to Emergency Departments because health needs are not clearly identified. Better information and support may help this population access services which match their needs and support their health more effectively.